การประยุกต์ใช้พอลิอีเทอร์อีเทอร์คีโตนในงานทันตกรรมประดิษฐ์ - เศรษฐะทัตต์ ไปรยา (วารสารการพยาบาล สุขภาพและสาธารณสุข, 2023)
The current trend is moving towards using metal-free restorations and biomaterials that exhibit advanced properties in the complex oral environment. Due to its excellent properties, such as stable chemical properties and biocompatibility, Polyetheretherketone (PEEK) has several applications in dentistry. The study aimed to summarize the experimental and clinical studies conducted about PEEK materials for applications in prosthodontics. Numerous studies have proven that PEEK can be successfully used in prosthodontics. PEEK could be considered a viable alternative material for removable partial dentures, fixed partial dentures, dental implants, and the restoration of maxillofacial defects. However, clinical studies are currently lacking, and further in-vitro and in-vivo studies are still needed to evaluate PEEK as a permanent material.